THERAPY DOGS AS A PREVENTIVE MEASURE FOR RABIES EXPOSURE AND MENTAL HEALTH ISSUES IN DEPLOYED TROOPS - Davenport, Jacob Monroe (My University, 2013)
I have been fortunate to gain an invaluable experience while completing my Masters of Public Health at the Fort Riley Military base. Under the direction of Dr. Paul Benne and many of his support staff I have learned many aspects and functionality of the day-to-day operations of a public health department. My general idea going into this experience was to learn more about mental health of military staff in the deployed environment and incorporating animal therapy programs into daily operations that would aide in the reduction of mental health related events. By interacting with animals in the deployed environment, the risk of rabies is of great concern for the safety of soldiers. Sadly, in the past the military has experienced a few cases of rabies transmission in active duty soldiers that have been exposed to infected animals. Incorporating animal therapy programs into a deployed environment would provide an alternative to soldiers seeking companionship from local dogs that have a high probability of being infected with Rabies.
Keywords: Public health; Human animal bond; Therapy dogs; Rabies; Public Health (0573)